Influence of Digital Game Influencers on Brand Engagement, Perceived Brand Value, and Purchase Intentions in Recommending Game Top Up Services - Mahardika, Maulana Rafi; Muslichah, Istyakara (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2025)
The influence of influencers has become one of the most effective marketing strategies, where influencers act as trusted figures for their audience when providing recommendations related to products or services. With their ability to shape perceptions, influencers play a key role in strengthening brand engagement, brand expected value, and purchase intention. This study aims to analyze the impact of perceived influence on brand engagement, brand expected value, and purchase intention, as well as examine the effects of brand engagement on brand expected value and purchase intention, and the impact of brand expected value on purchase intention. This research uses a survey method with a purposive sampling technique. A total of 160 respondents, who are active game players on social media and follow one of the game influencers in Indonesia, served as the subjects of the study. The data was analyzed using PLS-SEM, and the results showed a positive impact of perceived influence on brand engagement, brand expected value, and purchase intention. Brand engagement also positively affects brand expected value and purchase intention, while brand expected value has a positive impact on purchase intention. This study offers novelty by exploring the specific role of game influencers in influencing purchasing decisions, which has significant implications for digital marketing strategies.